The Roles of Tissue-Resident Memory T Cells in Lung Diseases - Yuan, Rui; Yu, Jiang; Jiao, Ziqiao; Li, Jinfei; Wu, Fang; Yan, Rongkai; Huang, Xiaojie; Chen, Chen (Frontiers in Immunology, 2021)
The unique environment of the lungs is protected by complex immune interactions. Human lung tissue-resident memory T cells (TRM) have been shown to position at the pathogen entry points and play an essential role fighting against viral and bacterial pathogens and antigens at the frontline through direct mechanisms and also by orchestrating the adaptive immune system through crosstalk. Recent evidence suggests that TRM cells also play a vital part in slowing down the carcinogenesis and preventing the spread of solid tumors. Less beneficially, lung TRM cells can promote pathologic inflammation, causing chronic airway inflammatory changes such as asthma and fibrosis. TRM cells from infiltrating recipient T cells may also mediate allograft immunopathology, hence lung damage in patients after lung transplantations. Several therapeutic strategies targeting TRM cells have been developed. This review will summarize recent advances in understanding the establishment and maintenance of TRM cells in the lung, describe their roles in different lung diseases, and discuss how the TRM cells may guide future immunotherapies targeting infectious diseases, cancers and pathologic immune responses.